Magnetic Nanoparticles for a New Drug Delivery System to Control Quercetin Releasing for Cancer Chemotherapy - Casagrande-Denardin, J (2011)
Quercetin belongs to the chemical class of flavonoids and can be found in many common foods, such as apples, nuts, berries, etc. It has been demonstrated that quercetin has a wide array of biological effects that are considered beneficial to health treatment, mainly as anticancer. However, therapeutic applications of quercetin have been restricted to oral administration due to its sparing solubility in water and instability in physiological medium. A drug delivery methodology was proposed in this work to study a new quercetin release system in the form of magnetite-quercetin-copolymer (MQC). These materials were characterized through XRD, TEM, IR, and Thermal analysis. In addition, the magnetization curves and quercetin releasing experiments were performed. It was observed a nanoparticle average diameter of 11.5 and 32.5 nm at Fe 3O 4 and MQC, respectively. The presence of magnetic nanoparticles in this system offers the promise of targeting specific organs within the body. These results indicate the great potential for future applications of the MQC to be used as a new quercetin release system. © 2011 Springer Science+Business Media B.V.